Компаративна студија на системите за заштита на децата жртви на полов напад во Република Северна Македонија и Република Словенија - Димеска, Наташа (Филозофски факултет, УКИМ, Скопје, 2022)
The position of the social worker as central to the management of child sexual abuse cases, especially in their coordination and child protection aspects is very important. Even if a social worker is not the person suspecting abuse or receiving a partial disclosure, social services will be informed on a duty basis. In the case of a partial disclosure, wherethe child's word is accepted as prima facie evidence of abuse, a social worker, together with the police, will initiate and pursue the investigation of what has happened, the family circumstances and relationships surrounding the child and questions of appropriate immediate protection. This is likely to include setting up a formal interview, which is most appropriately conducted conjointly by a trained social worker and a police officer. It may also be at this time that the first and crucial contact will be made with the child's caregivers or mother. At the subsequent case conference, an assessment of the safety of children in the family, as well as a plan for protection and therapy, will rely to a considerable extent on information gained by the social worker, under the same well-established procedure accepted for physical child abuse.
Докторска дисертација одбранета во 2022 година на Филозофскиот факултет во Скопје, под менторство на проф. д–р Иван Трајков.
Keywords: sexual abuse, child, social worker, investigation, interview